Psychological and adjustment problems due to acquired brain lesions in pre-school-aged patients. (June 2013) - Pastore, Valentina; Colombo, Katia; Villa, Federica; Galbiati, Susanna; Adduci, Annarita; Poggi, Geraldina; Massimino, Maura; Recla, Monica; Liscio, Mariarosaria; Strazzer, Sandra
Abstract Objective: To describe and compare psychological, behavioural and adjustment problems in pre-school patients with acquired brain lesions of different aetiology. Methods: Three groups of patients with acquired brain lesions (14 patients post-TBI, 18 brain tumour survivors and 23 patients with vascular or infectious brain lesions), ranging in age between 24–47 months, received a psychological evaluation, including the Child Behavior Checklist for Ages 2–3 (CBCL) and the Vineland Adaptive Behavior Scales (VABS). Results: About half of the total sample (47.2%) showed psychological and behavioural problems. Difficulties vary according to the aetiology of the brain lesions. Brain tumour survivors showed more marked internalizing problems, whereas children with vascular or infectious brain lesions scored higher on the CBCL externalizing scales. Children with traumatic brain injury reported intermediate scores on most of the CBCL scales. Conclusions: Psychological and behavioural difficulties are very common, not only among school-aged children and adolescents, but also among pre-schoolers with acquired brain lesions. The relevance and the impact of these difficulties must necessarily be considered when developing psychological treatment and rehabilitation plans and planning for social re-entry.